Efek Buah Kiwi (Actinidia Deliciosa) Sebagai Pengobatan Luka Bakar Derajat II - Agung Assirri (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Burns are injuries with the highest morbidity and disability in the hospital. Extensive and deep burn injuries are still the main cause of death. Children and parents are at risk for deeper burns because their dermis is thinner. Burns can be caused by touches of heat, electrical current or chemicals that affect the skin, mucosa, and tissues. Prevalence from 1997-2002 there were 17,237 children under 5 years received emergency treatment at 100 hospitals in America. The prevalence of burns in Indonesia is 2.2%. Burns can give fatal complications including shock conditions, infections, electrolyte fluid imbalances and respiratory distress. In addition to physical complications, burns can also cause severe emotional (trauma) and psychological distress due to disability and scars. Effective drugs for treating burns that have been widely known so far, such as silver sulfadiazine, bacitracin and mafenide acetate are anti-microbial agents. Kiwi (Actinidia deliciosa) is a plant that contains many phytochemical compounds such as flavonoids, triterpenoids, and quinone. In addition, kiwifruit has high levels of antioxidants and nutritional value, rich in vitamin C, fiber, calcium, iron, phosphorus and potassium and a higher phenolic content than strawberries, guava, papaya and starfruit which can treat wounds to second degree burns.